Reassembling Transformations for Robot Manipulators Characterised Using Network Theoretic and Clifford-Algebraic Methods. Issue 5 (10th May 2021) - Thiruvengadam, Sudharsan; Tan, Jei Shian; Miller, Karol
SUMMARY: A robotic manipulator's classical mechanical capabilities are governed by the design parameters (mass, geometry, dimensions, etc.) of its kinematic pairs and its architecture (number of limbs, degrees of freedom, actuation ability, etc.). Using Clifford-Algebraic and network theoretic methods, this work presents a novel-theoretical framework which allows any two robot architectures and design parameters to be mathematically related to one another through combinations of discrete operators or 'reassembling transformations'. Two theoretical case studies involving a 6R manipulator and Klann linkage are furnished in this work.